REPTILES AND THEIR ECOLOGY - Uzoqjonova Moxinur Diyorbek qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article provides brief information about the living conditions and distribution of reptiles, ecological groups. Reptiles live in different conditions compared to amphibians, many of which indicate that they are superior to them. Reptiles are true land-dwelling vertebrates. Their internal and external structures are complicated due to adaptation to dry land.